Effects of press coverage, information repetition and source reliability on audit opinion. - Cheong, Lin Hui. (2008)
Archival studies found that negative press coverage of an audit client increased the likelihood that auditors would issue a going-concern modified opinion. This study examines the potential influence of the analysts' comments, repetition of the same information with different source reliability on auditors' audit opinion decisions, going-concern judgments probability and perceived litigation risk.